The Dream of Sycorax in the Americas: Understanding Magical Realism in Indigo - Arargüç, Mehmet Fikret; Asayesh, Maryam Ebadi (Border Crossing, 2016)
Marina Warner’s Indigo retells The Tempest in the setting of Liamuiga and its main focus centers on giving a voice to the silenced female characters of The Tempest. Warner’s Sycorax is a shaman and adopts Dule/Caliban and Ariel, the children of slaves. The appearance of drowned slaves on the Liamuiga shoreline marks the beginning of Sycorax’s nightmare, forecasting the arrival of the English invaders whose first action is an attempt to burn Sycorax alive in her tree house. She survives, but later dies on the night of a bloody fight between indigenous islanders and the English. Her resting place becomes a shrine for the islanders, slaves and European inhabitants as her voice continues to be heard throughout the island. In this paper we intend to show how Warner uses the techniques of magical realist fiction to empower Sycorax and articulate her overarching dream of the return of peace and freedom to the colonized island of Liamuiga